An Analysis of the Phenomenon of Money Politics from a Political Communication Perspective in the 2024 Legislative Elections in Bandung City - Syauqi Syauqi; Neni Yulianita (Journal Research of Social Science, Economics, and Management, 2026)
This research is motivated by the persistent practice of money politics in the 2024 Legislative Election (Pileg) in Bandung City. Despite the implementation of regulations, such practices continue to occur with various patterns and strategies. The study aims to examine the process of money politics, the forms in which it is carried out, and the role of political communication in sustaining money politics during the 2024 Legislative Election in Bandung City. The research employed a qualitative case study approach within a constructivist paradigm. Data were collected through interviews, participant observation, and literature review. The findings reveal: (1) the process of money politics occurs through stages of voter mapping and targeting, distribution of money/goods during campaigns, and channeling through intermediaries; (2) money politics is carried out using money/goods due to its effectiveness and alignment with transactional political culture, through the construction of social facilities for image-building and long-term strategies, as well as social activities that utilize religious values and foster voter attachment; (3) political communication plays a role in shaping public opinion, reducing negative perceptions, and creating a positive image of candidates. Research on the phenomenon of money politics in the 2024 legislative elections in Bandung City shows that the practice of money politics is planned through voter mapping, incentive distribution, and channeling through intermediaries, with political communication that frames a narrative of concern and forms a positive image of the candidate to reduce public moral resistance.